2000
DOI: 10.1006/mthe.2000.0110
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Peptides with the Innate Immune System Studied with Use of T7 Phage Peptide Display

Abstract: The icosahedral T7 phage (diameter approximately 65 nm) displaying random peptides at the carboxy-terminus of the phage coat proteins was used as a model for drug and gene delivery vehicles containing peptide ligands. We found that displayed peptides were recognized by natural antibodies and induced complement activation. Strikingly, the phage inactivation by complement was peptide-specific that implied the existence of numerous natural antibodies with different peptide specificity. Selection of phage that avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
56
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 31 publications
6
56
0
Order By: Relevance
“…However, the LRP-mediated endocytosis of apoE-enriched chylomicron remnants, beta-VLDL, and LRP antibodies occurs largely in liver, where both hepatocytes and Kupffer cells are accessible to small particles due to vasculature fenestration Herz et al, 1990). The predominant occurrence of the LRP internalization activity in liver is consistent with our observations that up to 95% of T7 phage injected into mice is recovered from liver provided that the phage is rendered 'invisible' to natural IgM antibodies by removing its coat protein C-terminus (Sokoloff et al, 2000(Sokoloff et al, , 2003. Importantly, LRP expression is not observed in normal endothelial cells despite the presence in these cells of some LRP mRNA (Moestrup et al, 1992;Lupu et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…However, the LRP-mediated endocytosis of apoE-enriched chylomicron remnants, beta-VLDL, and LRP antibodies occurs largely in liver, where both hepatocytes and Kupffer cells are accessible to small particles due to vasculature fenestration Herz et al, 1990). The predominant occurrence of the LRP internalization activity in liver is consistent with our observations that up to 95% of T7 phage injected into mice is recovered from liver provided that the phage is rendered 'invisible' to natural IgM antibodies by removing its coat protein C-terminus (Sokoloff et al, 2000(Sokoloff et al, , 2003. Importantly, LRP expression is not observed in normal endothelial cells despite the presence in these cells of some LRP mRNA (Moestrup et al, 1992;Lupu et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…The new peptide display system is based on small phage T7 that easily penetrates through the space of Disse and presents displayed sequences at the p17 site that is evidently accessible to cell surface receptors (Sokoloff et al 2000). Our studies showed that the p17 display site was able to accommodate a wide variety of peptide sequences.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, while the substitution of the wild-type p17 sequence by a random sequence in a domain composed of perfectly aligned p17 chains would probably "break" its rod-like configuration and significantly reduce phage viability; the alignment shift is likely to mitigate the impact of such substitution. Peptide sequences are displayed in this system in a constrained configuration, which promotes selection of stable and efficacious ligands (Falciani et al 2005) and prevents the recognition of displayed sequences by natural antibodies (Sokoloff et al 2000). The avoidance of such recognition may be of paramount importance in designing therapeutically relevant delivery vehicles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations